PENGARUH MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP HASIL BELAJAR SENAM ROLL DEPAN (SISWA KELAS V MI AL-AZHAR MODUNG BANGKALAN - ARIFIN, BUSTANUL (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education seeks to help learners to use his body more efficient and proficient in basic skills and complex skills required in life. One lesson that was taught in school gymnastics is gymnastics floor foward roll. During this school have not used the audio visual in the learning process and just use the lecture method, demonstrations so researchers want to use the audio visual media in teaching and learning in schools to facilitate the teacher in explaining and guiding students in movement and the expected learning outcomes better than ever. In this research 2 times the test (pre-test and post-test) to grade V MI AL-Azhar in Modung Bangkalan time 3 meetings. in this study a sample to get treatment by introducing and implementing a media learning audio visual in teaching and learning. The research was conducted in 3 Time meeting. Type of research there is a quantitative approach experiment done strictly to determine a causal relationship between these variables. Of research and data processing of data obtained pre-test results gymnastic foward roll obtained the value 3170, the average value of 75.47, the lowest 60, highest score a 100, the standard deviation of 14,003. While the goal should Post-test exercise roll sum of the values ??obtained before 3420, the average value 81.43, the lowest 60, highest score a 100, the standard deviation of 11.959. In the t test (difference test) the results obtained by studying gymnastics foward roll with the results of statistical tests 0.001 it can be concluded there are significant differences between result study gymnastic foward roll pre test and post test. The conclusions of the study, namely audio visual learning media can improve learning outcomes gymnastics floor foward roll. Improved learning outcomes acquired gymnastic foward roll of 7,8%. Keywords: learning audio visual, gymnastics roll foward, learning outcomes